THE ROLE OF GOVERNMENT AND UNHCR IN PROMOTING EDUCATIONAL ACCESS FOR AFGHAN REFUGEES IN PAKISTAN - Hayat, Khizer; Ahmadi, Benafsha; Amirrachman, R. Alpha (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
Despite efforts by the government of Pakistan and the UNHCR to establish formal regulations and educational programs for Afghan refugee children, the results are mixed and unclear. On the one hand, these actions resulted in the enrollment of about 56,000 Afghan students and the placement of some refugee children in public schools. Meanwhile, overall enrollment fell from 55% in 2019-2020 to 18% in 2022-2023, demonstrating that, while legal and strategic frameworks exist, operational gaps, resource constraints, and cultural barriers continue to inhibit their effectiveness. This study aims to find out what the Pakistan’s government and UNHCR do within their legal frameworks and techniques to help Afghan refugees continue their education, and why the program is problematic. This research consider the Pakistan government's and UNHCR's legislative frameworks for expanding educational access for Afghan refugees and the implementation of these initiatives. The investigation examines UNHCR and government records to understand their service delivery goals. Economic concerns, school overcrowding, unequal opportunities for genders, and a lack of resources prevent children from achieving optimal growth. This study demonstrates that high-quality interventions, coordinated planning at all levels, and ongoing support enable Afghan refugees to receive a good education in their host nation. The study proposes improving education and making refugees feel more welcome in the Pakistani educational society.